2013
DOI: 10.1590/s1415-43662013000600002
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade de biomassa em sistemas agroflorestais e tradicionais no Cariri Paraibano

Abstract: As produtividades de biomassa de sistemas tradicionais (cultivos de milho e feijão, capim buffel ou palma) e agroflorestais (cultivos entre fileiras de gliricídia ou maniçoba) foram comparadas em experimento em parcelas subdivididas, de 2006 a 2009, em Taperoá, Paraíba. A precipitação média é de 600 mm. Nas parcelas agroflorestais as fileiras de árvores distavam 6 m, com 1 m entre árvores. No sistema tradicional, os cultivos produziram 33% mais biomassa e a biomassa de milho e feijão foi o dobro da produzida n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
(11 reference statements)
0
12
0
9
Order By: Relevance
“…Another possibility would be an inhibition of fixation due to the accumulation of N by the gliricidia plants in previous years. The intercropping of gliricidia, maize, and cowpea produced the highest amounts of aboveground biomass in the previous years (Martins et al, 2013) and probably also the highest amounts of belowground biomass. The decomposition of this biomass could increase the availability of mineral N, and it has been shown that high N availability reduces N fixation (Schipanski et al, 2010).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Another possibility would be an inhibition of fixation due to the accumulation of N by the gliricidia plants in previous years. The intercropping of gliricidia, maize, and cowpea produced the highest amounts of aboveground biomass in the previous years (Martins et al, 2013) and probably also the highest amounts of belowground biomass. The decomposition of this biomass could increase the availability of mineral N, and it has been shown that high N availability reduces N fixation (Schipanski et al, 2010).…”
Section: Resultsmentioning
confidence: 96%
“…Nitrogen concentrations in the legume plants (Table 2) were high in all systems, close to 4%, and the contents of N reflected the predominant effect of biomass production (Martins et al, 2013). Quantification of N in the straw is important, although seldom done in the region (Sampaio et al, 2004), because of its use as forage or because it is incorporated into the soil where it constitutes a net input to soil organic matter.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations